(untitled) (Nueva Epoca, 2020)
The legislative incorporation of personal rights and the consequent category of extra-patrimonial legal relations require a rethinking of the general theory of institutes as the legal act. The current regulations are analyzed by projecting them on the precepts of the legal act, addressing two specific emergencies such as the autonomy of the will and representation.